Analisis Pengaruh Solvabilitas, Profitabilitas dan Kualitas Auditor Terhadap Penerimaan Opini Audit Going Concern - Isabella Nadia Anjani; Mira Kartika Dewi Djunaedi (KALBISIANA Jurnal Sains, Bisnis dan Teknologi, 2023)
The purpose of this study was to determine the effect of solvency, profitability, and audit quality on going concern opinions. The independent variables in this study are solvency, profitability, and audit quality. Meanwhile, the dependent variable is going concern opinion. This study uses secondary data using data from the Indonesia Stock Exchange, testing using .And in this study shows that solvency, profitability and audit quality affect going concern opinion. This test uses convenience sampling, with a total sample of 120 companies. The method used is the Logistics Regression test with the use of Eviews 10. The results in this study indicate that the solvency is not significant with a negative coefficient direction. Profitability is not significant with a negative coefficient direction. Auditor quality is not significant with positive coefficient direction